Tax Aggressiveness: Transfer Pricing, Gender Diversity and Independent Commissioners’ Roles - Pratama, Aliya; Ristiyana, Rida; Sani, Abdillah (GOVERNORS, 2025)
The focus of this study is to determine the impact of transfer pricing, gender diversity and independent commissioners on tax aggressiveness with company value as a mediating variable. A type of quantitative research using secondary data through the company's financial statements. The research population is multinational companies in the manufacturing sector listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique uses purposive sampling with a sample of 22 companies. The data analysis method uses panel data regression analysis processed with e-views software 13. The results of the simultaneous study of transfer pricing, gender diversity and independent commissioners have a significant impact on tax aggressiveness. The results of the study partially showed that independent commissioners had a positive and significant effect on company value, while transfer pricing and gender diversity had no effect on company value. On the other hand, gender diversity has a negative and significant effect on tax aggressiveness, while transfer pricing, independent commissioners, and company value have no effect on tax aggressiveness. The results of the mediation effect test show that the value of the company cannot mediate the influence of transfer pricing, gender diversity and independent commissioners on tax aggressiveness.